One-pot three-component synthesis of 1, 2, 3-triazoles using magnetic NiFe2O4–glutamate–Cu as an efficient heterogeneous catalyst in water1. Issue 73 (9th August 2015) - Lu, Jun; Ma, Er-Qian; Liu, Yu-Heng; Li, Ya-Meng; Mo, Li-Ping; Zhang, Zhan-Hui
<x xml:space="preserve">Abstract</x> A magnetic NiFe2O4 supported glutamate–copper catalyst is prepared and applied for the synthesis of a wide variety of 1, 2, 3-triazoles in water at room temperature.